Toxic effects of cadmium (Cd) on anaerobic biomass: Kinetic and metabolic implications - Mockaitis, G.; Rodrigues, J.A.D.; Foresti, E.; Zaiat, M. (Journal of Environmental Management, 2012)
Cadmium ion (Cd) toxicity on anaerobic systems, used for organic matter removal, was assessed by studying its effect on kinetic parameters and metabolic changes. This fundamental study was performed in a continuous fixed bed anaerobic bioreactor that treated synthetic wastewater simulating domestic sewage. The biomass was immobilized on a fixed bed made of polyurethane foam. Under influent cadmium concentrations of 0.0, 0.4, 4.4 and 6.2 mg Cd L the organic matter removal efficiencies were 84%, 82%, 72% and 52%, respectively. At influent concentration of 6.2 mg Cd L the reactor had reached its limit for cadmium toxicity. In the removal of dissolved organic matter, the first-order apparent kinetic coefficients () were 0.84, 0.67 and 0.10 h for the operations with 0.0, 0.4 and 4.4 mg Cd L, respectively. The apparent inhibition coefficient for cadmium () was 1.69 mg L. Despite the toxic effects of cadmium on anaerobic organic matter removal at large Cd concentrations, the results demonstrated that the anaerobic process was suitable for cadmium concentrations below 29.8 mg Cd L, considering the bioavailable fraction of adsorbed cadmium in the support when the cadmium influent concentration was 6.2 mg Cd L.